2019
DOI: 10.11591/ijece.v9i1.pp629-634
|View full text |Cite
|
Sign up to set email alerts
|

A review on various optimization techniques of resource provisioning in cloud computing

Abstract: <span lang="EN-US">Cloud computing is </span><span lang="EN-AU">the provision of IT resources (IaaS) on-demand using a pay as you go model over the internet</span><span lang="EN-US">.It is a</span><span lang="EN-AU"> broad and deep platform that helps customers builds sophisticated, scalable applications.</span><span lang="EN-US"> To get the full benefits, research on a wide range of topics is needed. While resource over-provisioning can cost users more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, it is observed that turning of processor might not be necessary to reduce the energy consumption, hence they proposed energyaware processor merging (EPM) mechanism to choose the particular processor to switch off for energy consumption and quick-EPM was developed to minimize the computational overheads. In [22] proposes cost and energy aware scheduling (CEAS) technique for the cloud scheduler to reduce the workflow execution cost and minimize the energy consumption which meets the deadline prerequisite. In general, CEAS comprises five algorithms, at first virtual machine (VM) selection approach is used that applies the cost utility concept to map the task to their optimal VM-types through the make span constraint.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, it is observed that turning of processor might not be necessary to reduce the energy consumption, hence they proposed energyaware processor merging (EPM) mechanism to choose the particular processor to switch off for energy consumption and quick-EPM was developed to minimize the computational overheads. In [22] proposes cost and energy aware scheduling (CEAS) technique for the cloud scheduler to reduce the workflow execution cost and minimize the energy consumption which meets the deadline prerequisite. In general, CEAS comprises five algorithms, at first virtual machine (VM) selection approach is used that applies the cost utility concept to map the task to their optimal VM-types through the make span constraint.…”
Section: Literature Surveymentioning
confidence: 99%
“…Edge computing paradigm (or similar platforms as Mobile Edge Computing (MEC), fog computing or cloudlet) was introduced, due to the fact that the mobile and IoT applications demands and resources requirements have increased, e.g. ; computing platforms [1][2][3][4][5]. Consequently, the necessity of a new platform that supports these applications demands within a close proximity of computational and storage resources, within a geographically distributed area, are really a necessity.…”
Section: Introductionmentioning
confidence: 99%